PENDIDIKAN AGAMA PADA ANAK OLEH ORANG TUA (Periode Masa Anak-Anak, Tinjauan Psikologi Agama) - Ahmad Yani (Wardah, 2013)
This paper attempts to discuss the things that can be done by parents in providing the religious education to their children  in the period of childhood (age 0-12 years). Parents as primary educators in the family have a function and a strategic role in providing religious education to their children. Providing the religious education to children in family must be done by parents seriously because a child is a mandate given to parents from Allah Almighty. In providing religious eduation to  children must go through the stages in accordance with the growth and the development of the children physically and mentally. Thus, providing religious education to their children  in the period of childhood is very important. It will influence the character and personality of children for the future.